The Effect Of Company Size, Liquidity, And Leverage On Company Value With Dividend Policy As An Intervening Variable - oryzea nathasya handayani (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to analyze the influence of company size, liquidity, and leverage on company value with dividend policy as an intervening variable in non-cyclical consumer sector companies listed on the IDX for the 2020-2022 period. This type of research is quantitative research and the data used is secondary data. the population in this research is 123 on cyclicals consumer sector companies listed on the IDX during the 2020-2022 period. Using a purposive sampling method, this research has a sample of 66 companies. The data analysis techniques used are descriptive statistical analysis, inner model analysis, and hypothesis testing with the help of SmartPLS 3. The research results show that Liquidity and Leverage have a significant negative effect on Company Value. Company Size and Dividend Policy have np significant effect on Company Value. Company Size has a significant positive effect on Dividend policy. Liquidity and Leverage have no effect on Dividend Policy. Meanwhile, Company Size, Liquidity, and Leverage have no effect on Company Value with Dividend Policy as an intervening variable.